Penerapan Restorative Justice dalam Perkara Tindak Pidana Penipuan dan Penggelapan di Tingkat Prapenuntutan - Silaban, Josua Ferdinand; Latupeirissa, Julianus Edwin; Leasa, Elias Zadrack (Faculty of Law Universitas Pattimura, 2025)
The Restorative Justice approach is a milestone in the renewal of the criminal law system reform towards a positive direction. However, currently, the Indonesian criminal law system has not accommodated a comprehensive explanation of the definition, principles, and application of criminal acts based on restorative justice at the level of the Law and Restorative Justice is still interpreted narrowly as the termination of the case. The method that will be used by the researcher is Normative Judicial. The type of research is descriptive analysis. The sources of legal materials used are primary, secondary and tertiary legal materials. Data collection techniques through literature studies. The results of the study explain that the application of Restorative Justice in Indonesia can be applied to several categories of criminal acts and can be applied at every stage in criminal justice by considering a number of factors and Restorative Justice is a complement to the current criminal law system. Settlement of cases with a peace agreement in cases of fraud and embezzlement is one of the efforts of victims to obtain compensation from the perpetrators, but the process has not been clearly regulated at the pre-prosecution level.